Culture of spermatogonial stem cells and use of surrogate sires as a breeding technology to propagate superior genetics in livestock production: A systematic review - Nakami, W.; Kipyegon, A.N.; Nguhiu-Mwangi, J.; Tiambo, Christian K.; Kemp, Stephen J. (Veterinary World, 2021)
Background and Aim: Spermatogonial stem cells (SSCs) have previously been isolated from animals' testes, cultured in vitro, and successfully transplanted into compatible recipients. The SSC unique characteristic has potential for exploitation as a reproductive tool and this can be achieved through SSC intratesticular transplantation to surrogate sires. Here, we aimed at comprehensively analyzing published data on in vitro maintenance of SSC isolated from the testes of livestock animals and their applications. Materials and Methods: The literature search was performed in PubMed, Science Direct, and Google Scholar electronic databases. Data screening was conducted using Rayyan Intelligent Systematic Review software (https://www.rayyan.ai/). Duplicate papers were excluded from the study. Abstracts were read and relevant full papers were reviewed for data extraction. Results: From a total of 4786 full papers screened, data were extracted from 93 relevant papers. Of these, eight papers reported on long-term culture conditions (>1 month) for SSC in different livestock species, 22 papers on short-term cultures (5-15 days), 10 papers on transfection protocols, 18 papers on transplantation using different methods of preparation of livestock recipients, and five papers on donor-derived spermatogenesis. Conclusion: Optimization of SSC long-term culture systems has renewed the possibilities of utilization of these cells in gene-editing technologies to develop transgenic animals. Further, the development of genetically deficient recipients in the endogenous germline layer lends to a future possibility for the utilization of germ cell transplantation in livestock systems.